Implementasi Pemebelajaran Bahasa Indonesia Berbasis Karakter Bersahabat dan Komunikatif di SD/MI - Yudiyanto, Mohamad; Mulyani, Ani Sri; Kusnadi, Roni (Peneliti.net, 2022)
Character education is not just about what we know, but also about how we behave and act in everyday life. This study aims to elaborate the implementation of friendly and communicative character-based Indonesian learning. The research method used is library research using a qualitative approach. The results showed that the implementation of friendly and communicative character-based Indonesian learning also strengthened collaboration and social interaction between students. They learn to work together, share ideas, and build positive relationships with fellow students. Students tend to be more engaged and motivated in learning Indonesian that are character-based, friendly, and communicative. They feel more engaged because the learning material is relevant to everyday life and promotes values that are meaningful to them. Implementing Indonesian learning that emphasizes friendly and communicative character also helps strengthen students' national identity